Reactive Seizures Due to Hyperlipidemia in a Maltese Dog - de Sales, Nathali Adrielli Agassi; Picelli, Julia Perinotto; Alves, Endrigo Gabellini Leonel; dos Anjos, Luana Castela de Tacia; Bittar, Eustáquio Resende; Rosado, Isabel Rodrigues (Acta Scientiae Veterinariae, 2021)
Background: Primary hyperlipidemia is a condition that affects some specific breeds. It has been previously described in Miniature Shnauzer, Beagles, Shetland Shepdog and West Highland White Terrier. There are no reports of primary hyperlipidemia in Maltese dogs. It is a hereditary disorder of lipoprotein metabolism. The etiology is unknown and may be related to a genetic problem in lipoprotein lipase or to the absence of apaprotein CII. Clinical signs include spontaneous arterosclerosis, retinal lipemia, cutaneous xanthomas, abdominal pain, lethargy, vomiting and / or diarrhea. Neurological manifestations such as seizures and behavioral changes may also occur. The aim of this report is to describe a case of reactive seizures due to hyperlipidemia in a dog. Case: A 5-year-old male Maltese dog was admitted with a history of seizures. Hypertension and abdominal distension with large amounts of intestinal gases were found in general physical examination. Neurological examination revealed impaired nasal septum sensory perception, which was slightly bilaterally reduced, and pain on cervical palpation and in the brachial plexus region. Based on history and clinical examination, it was possible to locate the lesion in the thalamocortical region and to suspect idiopathic epilepsy, reactive seizures, and symptomatic epilepsy due to meningoencephalitis of unknown origin. The diagnosis of primary hyperlipidemia was made by exclusion with the aid of laboratory tests and ultrasound. After the establishment of a fat restriction diet, bezafibrate, phenobarbital, and omega-3 supplementation, the animal improved significantly with the reduction of epileptic seizures. Discussion: The initial clinical suspicion was hyperadrenocorticism as the primary cause of hyperlipidemia. This suspicion was based on the presence of polyphagia, polydipsia, polyuria and abdominal distension, together with laboratory results of thrombocytosis, increased ALT and AF, and hyposenuria; but ultrasound images and ACTH stimulation test ruled out this differential diagnosis. Hypothyroidism was also ruled out since LDL values were normal and the animal was extremely active. Regarding nephrotic syndrome, it was also excluded for some alterations would be present, such as severe proteinuria, cholesterol reduction and hypoalbuminemia. As for diabetes mellitus, it was discarded because of the dog’s young age and due to the absence of suggestive clinical signs. The suspicion of primary hyperlipidemia was based on increased levels of triglycerides, and the presumptive diagnosis was of reactive seizures due to hyperlipidemia. It is essential, when treating hyperlipidemia, to readjust to a low-calorie diet with fat concentration below 8% and protein level above 18%. Generally, these restricted diets are for life. Omega-3 supplementation can be performed to help maintain low levels of triglycerides. Drug therapy is usually carried out with bezafibrate, which is used in human medicine as treatment for hypertriglyceridemia, and has showed good results in the control of hypertriglyceridemia and hypercholesterolemia in dogs with primary and secondary hyperlipidemia. Six months after the beginning of the treatment, the animal no longer presented abdominal distension and pain, cholesterol values and its fractions were controlled, as well as triglycerides. Seizures were also under control. Therefore, hyperlipidemia is an important differential diagnosis in cases of patients presenting seizures, especially when dealing with young animals showing signs of metabolic diseases.